Julian Saba, 'Father of the Monks' of Syria - Griffith, Sidney Harrison (Journal of early Christian studies, 1994)
Julian Saba (d. 367) is the earliest person in the Syriac-speaking community whose name we know, who dedicated himself to the eremitical life. His story has been preserved for us in Theodoret's History of the Monks of Syria, in a collection of Syriac poems attributed to Ephraem (306-373), and in a Syriac memra attributed to Jacob of Serug (ca. 450-ca. 520). Based on these sources, the present article gives an account of Julian's fame in Syria, and explores the significance of his accomplishments for the history of monasticism in the Syriac-speaking regions of the Early Christian world.